LibreOffice Calc: працюємо з електронною таблицею - Петренко, Олександр Якович (My University, 2014)
This textbook contains an in-depth study and practical mastering the basic techniques for working with the spreadsheet LibreOffice Calc. The manual is intended for postgraduate education of specialists of food and processing industry, a wide range of professionals and students working with spreadsheets.
Keywords: обчислення; клітини; електронна таблиця; calculations; cells; spreadsheet